2010
DOI: 10.1007/s11540-010-9167-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of MSW Compost and Fertilizer on Extractable Soil Elements, Tuber Yield, and Elemental Concentrations in the Plant Tissue of Potato

Abstract: Municipal solid waste (MSW) compost is readily available in eastern Canada and may be a good source of fertility. A 3-year experiment evaluated the effects of MSW compost and fertilizer on soil fertility, elemental composition and yield of potato (Solanum tuberosum L.) grown in a sandy loam soil. Three rates of compost (MSW1, MSW2, and MSW3), one rate of fertilizer (NPK), and one mixture of 1/2 MSW1 compost and 1/2 NPK fertilizer were applied annually to plots in a three-crop rotation; each year the MSW1 rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Potato N use efficiency varied from 193 to 258 kg yield kg (Table 11). This finding is consistent with other studies that reported enhanced potato apparent N recovery when combining GMs or other organic amendments such as manures or composts with mineral N fertilizer [56,64].…”
Section: Nitrogen Uptake Nitrogen Recovery and Nitrogen Fertilizer supporting
confidence: 93%
See 1 more Smart Citation
“…Potato N use efficiency varied from 193 to 258 kg yield kg (Table 11). This finding is consistent with other studies that reported enhanced potato apparent N recovery when combining GMs or other organic amendments such as manures or composts with mineral N fertilizer [56,64].…”
Section: Nitrogen Uptake Nitrogen Recovery and Nitrogen Fertilizer supporting
confidence: 93%
“…Contrast analysis showed that higher N uptake occurred when potato succeeded summer GMs than cereals or fall GMs. Earlier studies showed that slow release of N from green manure residues are better synchronized with plant N uptake than inorganic N fertilizer [9,12,64], and could result in increasing N uptake efficiency. Therefore, discrepancies between preceding crops in this study may reflect poorer or better synchrony between N supply from residue decomposition with active potato N uptake.…”
Section: Nitrogen Uptake Nitrogen Recovery and Nitrogen Fertilizer mentioning
confidence: 99%
“…cicla L.) and basil (Ocimum basilicum L.), Zhelzaskov and found that MSWC applied at 200, 400, or 600 kg/l increased the concentration of Cu and Zn in soil, but uptake by plants was not observed. Marketable yield of potato was as high as regular NPK fertilizer, only in the second and third years after the application of MSWC (Warman et al 2011). In this study, the effect of choice of substrate on changes in the physicochemical properties of the hydroponic medium was not assessed.…”
Section: Yield and Fruit Propertiesmentioning
confidence: 85%
“…Table 1 shows different studies on agricultural utilization of MSWM. Warman et al (2011) studied comparative response of MSWC and IF on potatoes grown in a 3-year rotation including winter squash and sweet corn at Nova Scotia, Canada. The doses were NPK 130-63-68 (1996);130-65-59 (1997) and 130-75-68 kg ha -1 (1998); NK 130-0-59 kg ha -1 (1997); MSWC were applied at three rates (MSW1, MSW2 and MSW3) 21.7, 43.4, 65.1 Mg ha -1 (1996);11.3, 22.6, 33.9 Mg ha -1 (1997);8.9, 17.8, 26.7 Mg ha -1 (1998); and MIX = 0.5 MSW1 ?…”
Section: Agricultural Utilization Of Msw Compostmentioning
confidence: 99%